Konflikhantering as bestuurstaak in 'n multikulturele onderwysopset - Steenkamp, S. W. B.(Schalk Willem Burger) (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Ed.) -- Universiteit van Stellenbosch, 1993.